Исследование технологических параметров процесса получения чугунных отливок для работы в условиях износа - Лукьяненко, И.В. (Металл и литье Украины, 2019)
В работе дано подробное описание состояния вопроса, который касается актуальности повышения износостойкости деталей машин и механизмов, работающих в условиях интенсивного абразивного и ударно-абразивного износа. Изложены основные актуальные направления решения этой проблемы. Высветлены преимущества использования биметаллов в мировой и отечественной практике, а также приведены основные группы методов, которые характеризуются общностью технологических приемов, производства биметаллов и многослойных материалов с использованием технологий литья. У роботі дано детальний опис стану питання щодо актуальності підвищення зносостійкості деталей машин і механізмів, які працюють в умовах інтенсивного абразивного і ударно-абразивного зношування. Викладено основні актуальні напрямки вирішення цієї проблеми. Висвітлено переваги використання біметалів у світовій і вітчизняній практиці, а також наведено основні групи методів, які характеризуються спільністю технологічних прийомів, виробництва біметалів і багатошарових матеріалів з використанням ливарних технологій. The paper provides a detailed description of the state of the issue, which concerns the relevance of improving the wear resistance of machine and mechanisms parts operating under conditions of intense abrasive and impact-abrasive wear. The basic actual directions of the solution of this problem are stated. The advantages of using bimetals in the global and domestic practice are highlighted, and the main groups of methods that are characterized by common technological methods, production of bimetals and multilayer materials using casting technologies are given.
The paper provides a detailed description of the state of the issue, which concerns the relevance of improving the wear resistance of machine and mechanisms parts operating under conditions of intense abrasive and impact-abrasive wear. The basic actual directions of the solution of this problem are stated. The advantages of using bimetals in the global and domestic practice are highlighted, and the main groups of methods that are characterized by common technological methods, production of bimetals and multilayer materials using casting technologies are given.